PENGARUH Azotobacter sp., MVA, DAN PUPUK NITROGEN TERHADAP KEPADATAN Azotobacter sp., DERAJAT INFEKSI AKAR DAN KETERSEDIAAN N DAN P TANAH PADA ULTISOL - Nana Danapriatna (PARADIGMA : JURNAL ILMU PENGETAHUAN AGAMA, DAN BUDAYA, 2002)
A research to study the effect of Azotobacter sp., VAM, and nitrogen fertilizer on Azotobacter sp. density, root infections degree, and soil available N and P was conducted in green house of Fakultas Pertanian, Universitas Padjadjaran at Jatinangor and Soil and Plant Laboratory of Balitsa at Lembang from December 1996 to June 1997 Result of the experiment showed that effect of increased of nitrogen fertilizer dosage on Azotobacter sp. density, soil available N-NO3 and P was depend on applied microbial inoculants. Effect of increased of nitrogen fertilizer dosage on root infections degree* soil available N-NH4 was not depend on applied microbial inoculants. Inoculations MVA was increased root infections degree of tomato, whatsoever nitrogen fertilzer dosage was applied